Case report: Atlantoaxial instability and subluxation in a dog with Ehlers–Danlos syndrome - Choi, Simon; Sullivan, Louise; Long, Sam (Frontiers in Veterinary Science, 2023)
Ehlers-Danlos syndrome is a rare, heritable connective tissue disorder characterized by soft, hyperextensible skin, joint hypermobility and tissue fragility, the severity of which can range from mild to severe. A 9 month-old male entire miniature dachshund was presented following peracute tetraparesis. Neurological examination was suggestive of intracranial vestibular disease or high cervical myelopathy. MRI revealed atlantoaxial instability and subluxation resulting in marked spinal cord compression at C1-C2 which was surgically stabilized. On discharge from hospital, skin fragility was noted as the result of skin tearing during tape removal. A piece of full thickness antebrachial skin was submitted for histopathology which showed changes consistent with Ehlers-Danlos syndrome. This case report describes the first case of atlantoaxial instability and subluxation in a dog as the result of a confirmed underlying collagenopathy.